Non-disclosed men who have sex with men within local MSM HIV-1 genetic transmission networks in Guangyuan, China - Zhuoma, Lacuo; Zhang, Yan; Yan, Tu; Kang, Fayang; Hou, Xueqin; Chen, Jianguo; Huang, Min; Zeng, Yali; Wang, Qiushi; Zhou, Chang; Liang, Shu; Su, Ling (Frontiers in Public Health, 2022)
Background: Most men who have sex with men (MSM), especially with HIV infection, do not disclose their sex-same behaviors in China due to Chinese family values and fear of stigmatisation, rejection, or prejudice. However, disclosure of same-sex behaviors to healthcare providers (HCPs) can be beneficial for reducing viral transmission and promoting their physical and mental health. Here, by combining phylogenetic analysis with traditional epidemiological approaches, we tried to identify the MSM who do not disclose to HCPs in transmission networks and explored the factors related to the non-disclosed behaviors. Method: Phylogenetic analysis was conducted using HIV pol sequences obtained from the drug resistant surveillance program, which was collected as part of the routine clinical care since 2012. Sequences were linked to the demographic data collected in the Chinese HIV/AIDS Comprehensive Response Information Management System (CRIMS). Firstly, those male patients, of which genetic sequences were within the molecular transmission clusters involving self-reported MSM, were identified as potential MSM (pMSM). Then, a cross-sectional survey was conducted to supplement behavioral information and attitudes towards MSM. Results: Our sample consisted of 190 pMSM patients in our study. 43.16% of the patients were likely to conceal same-sex behaviors during the first-self-report, and 14.73% patients might continue to conceal history of same-sex behaviors even after receiving medical care. The pMSM who concealed their same-sex behaviors were reluctant to accept medical services such as Voluntary Counselling and Testing (VCT) and had a lower likelihood of condom use. In addition, the related factors for non-disclosed behavior were associated with current address, income before diagnosis, and attitudes towards MSM. Conclusion: Non-disclosure of same-sex behaviors to HCPs may be a major obstacle for certain medical services of MSM and exhibit risky sexual behaviors. The pMSM from developing areas, with high monthly income, and with neutral or un-supportive attitudes towards MSM may represent non-disclosure of their same-sex behaviors. Thus, policies facilitating MSM to disclosure their same-sex behaviors are recommended, such as legislations protecting homosexual rights on employment, education, marriage and so on.